Can inflammation be resolved in Alzheimer's disease?. (August 2018) - Zhu, Mingqin; Wang, Xiuzhe; Sun, Li; Schultzberg, Marianne; Hjorth, Erik
Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive memory loss and dementia. Accumulating evidence suggests that inflammation is involved in the pathogenesis of AD. Epidemiological studies suggest that use of anti-inflammatory drugs is associated with a lower incidence of AD. However, clinical trials with anti-inflammatory drugs have not been successful. Recent studies have shown that inflammation is resolved by a process that is mediated by a group of lipid mediators, so called specialized pro-resolving lipid mediators (SPMs). Unlike anti-inflammatory strategies, which usually involve inhibition of the synthesis of inflammatory mediators, stimulating the resolution of inflammation is aimed at ending inflammation in a similar fashion as under normal physiological conditions. We have previously shown that pathways of resolution are impaired in AD. Moreover, we found that SPMs can improve neuronal survival and increase microglial phagocytosis of amyloid beta (Aβ) in in vitro studies, indicating that stimulating resolution of inflammation may be a potential therapeutic target in AD. In this review, we summarize recent findings regarding resolution of inflammation in AD. We also discuss possible strategies to stimulate the resolution of inflammation in AD, specifically focusing on signaling pathways, including SPMs, their receptors and enzymes involved in their formation.